2017
DOI: 10.1002/smj.2725
|View full text |Cite
|
Sign up to set email alerts
|

Strategy as staged performance: A critical discursive perspective on keynote speeches as a genre of strategic communication

Abstract: Research Summary: In this article, we explore how keynote speeches come into being as a staged genre of strategic communication. In our critical discursive analysis of video data on Apple Inc.'s keynote speeches, we demonstrate how keynote speeches are multimodally accomplished through the embodied enactment of four discursive practices: referencing, relating, demarcating, and mystifying. We show how different bodily movements, which we describe as leveling and leaping gestures, systematically contribute to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 55 publications
1
51
0
1
Order By: Relevance
“…Despite the potential of visuals-based studies, studies in strategic management have mostly focused on the role of discourse in the strategy process (Balogun et al, 2014;Heracleous and Barrett, 2001;Mantere, 2013;Mantere and Vaara, 2008;Vaara, 2010) with awareness of, but limited attention to, the precise mechanisms through which visual modes of communication could result in varying strategic outcomes. These outcomes are of growing importance to strategic management scholarship due to growing sophistication in the use of tools (Jarratt and Stiles, 2010;Jarzabkowski and Kaplan, 2015), body language (Gylfe et al, 2016;Liu and Maitlis, 2014;Wenzel and Koch, 2018) and other visual artefacts, such as the cube employed by RetailCo to support their new strategy process (Whittington, Molloy, Mayer and Smith, 2016), as well as the recognition that interactions between different modes can have important effects that help determine which strategies are ultimately implemented (Spee and Jarzabkowski, 2011;Stigliani and Ravasi, 2012). Following the aim of our chapter to offer insight for Open Strategy debates, we have developed a broad categorisation of this emerging group of visual strategy studies to then relate them to Open Strategy in the section that follows.…”
Section: Visual Focus In Strategy Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential of visuals-based studies, studies in strategic management have mostly focused on the role of discourse in the strategy process (Balogun et al, 2014;Heracleous and Barrett, 2001;Mantere, 2013;Mantere and Vaara, 2008;Vaara, 2010) with awareness of, but limited attention to, the precise mechanisms through which visual modes of communication could result in varying strategic outcomes. These outcomes are of growing importance to strategic management scholarship due to growing sophistication in the use of tools (Jarratt and Stiles, 2010;Jarzabkowski and Kaplan, 2015), body language (Gylfe et al, 2016;Liu and Maitlis, 2014;Wenzel and Koch, 2018) and other visual artefacts, such as the cube employed by RetailCo to support their new strategy process (Whittington, Molloy, Mayer and Smith, 2016), as well as the recognition that interactions between different modes can have important effects that help determine which strategies are ultimately implemented (Spee and Jarzabkowski, 2011;Stigliani and Ravasi, 2012). Following the aim of our chapter to offer insight for Open Strategy debates, we have developed a broad categorisation of this emerging group of visual strategy studies to then relate them to Open Strategy in the section that follows.…”
Section: Visual Focus In Strategy Researchmentioning
confidence: 99%
“…Furthermore, as video ethnographers have demonstrated (LeBaron and Streeck, 1997), the embodied interactions can be captured in visual form and analysed (Wenzel and Koch, 2018). Indicative of this is the study by Werle and Seidl (2015) who examined strategy workshops and showed how discursive practices were provoked as participants compared differences between partially completed documents.…”
Section: Cognitive Focusmentioning
confidence: 99%
“…In other settings, the reverse is true. In analyzing the business keynote speeches of Steve Jobs, Wenzel and Koch (2018) described the central role of expressive gestures. However, during the examined keynote speeches, gestures did not play a strong pragmatic role, and audience members could only exhibit collective affiliation with the message by applauding or cheering.…”
Section: Protocol For Gesture Analysis In Naturalistic Settingsmentioning
confidence: 99%
“…By close examination of micropractices, strategy as practice researchers show how all kinds of details can shift the outcomes of strategizing work. Small things make a difference, whether it is the deft use of strategy discourse (Balogun et al 2014, Wentzel andKoch 2017), the artful sequencing of agendas (Jarzabkowski and Seidl 2008), the manipulation of standard strategy tools (Kaplan 2008, Knight et al 2017, control over emotion and exhaustion (Clarke et al 2012, Liu andMaitlis 2014,), the location of strategy retreats (Johnson et al 2010), or even the choice of seating positions (Jarzabkowski et al 2015b). This kind of strategy as practice research helps make the manager a shrewder strategy practitioner, able to dodge distractions, and outmanoeuvre rivals in order to advance his or her own agendas.…”
Section: From Theory To Practicementioning
confidence: 99%